Monkey see, monkey do: A comparison of the attitudes of top and purchasing managers to corruption in business - L. Pitt; D. Nel; P. De Wit (South African Journal of Business Management, 1989)
This article describes a comparative survey of the attitudes of top and purchasing managers regarding the extent to which their attitudes towards corrupt and possibly corrupt business behaviour differs. The extent of perceived peer group participation in deviant activities is also measured. The results of the research indicate that while there is little or no difference between the groups regarding attitude and perceived participation measures, there is a marked difference between the attitudes for both groups and the perceived participation of their peers. The need for top management action on policy in this regard is emphasized.
Keywords: 650